A Comprehensive Review of Antibiotic Resistance: Mechanisms, Causes, and Novel Therapeutic Approaches - Prit Sunilbhai Patel; Amar M. Raval; Patel Annavi Ashish Kumar; Patel Poorv Dharmendra Kumar; Prajapati Tushar Ghanshyam; Patel Pankti bhavikkimar (Asian Journal of Pharmaceutical Research and Development, 2026)
Antibiotic resistance is a major global health concern that threatens the effective treatment of bacterial infections. The misuse and overuse of antibiotics in human medicine and agriculture have accelerated the emergence of resistant bacterial pathogens such as Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Various mechanisms, including genetic mutations and horizontal gene transfer, contribute to the spread of antimicrobial resistance. This review discusses the causes and mechanisms of antibiotic resistance as well as emerging strategies to combat it, including bacteriophage therapy, antimicrobial peptides, and advanced genomic technologies. Strengthening antimicrobial stewardship, improving surveillance systems, and developing new therapeutic approaches are essential to control the spread of antibiotic resistance and ensure effective treatment in the future.